Sexism in political discourse: a case study - Soriano-Jiménez, Carlos (My University, 2023)
It can be argued that language not only reflects gender inequalities but that it is also a key tool to perpetuate, shape and create these inequalities (Graddol & Swann, 1989, p. 9). However, in recent decades, the use of gender-neutral language has been viewed as an imposition by those who criticize political correctness and consider it to be “an excessive attention to the sensibilities of those who are seen as different to the norm (women, lesbians, gays, disabled people, black people)” (Mills, 2008, p. 100). As a consequence, it has been frequently perceived by some as an attack towards freedom of speech. During the 2016 United States electoral campaign, former Republican President Donald Trump openly criticized political correctness and, at the same time, defended himself from accusations of sexism: “Nobody has more respect for women than I do. Nobody” (Bloomberg Quicktake, 2016). To what extent is this claim true? The main aim of this paper is to analyze how Donald Trump uses sexist language to belittle women and reinforce gender stereotypes in his political discourse. The theoretical framework of the present investigation for detecting sexism in discourse draws on Mill’s model (2008, pp. 41-76) and the Ambivalent Sexist Theory put forward by Glick and Fiske (1997, pp. 119-135). The former model draws a distinction between overt and indirect sexism, whereas the latter shows that sexist discourse can be expressed in two different ways, benevolent and hostile sexism. The research data come from a wide range of audiovisual sources from 2015 to 2020, including fragments of rallies, TV shows and the 2016 presidential debates. Three areas of discussion are examined: the portrayal of the role of women in society, the categorization of women in terms of their appearance and lack of strength, and insult terms.
Keywords: Sexismo en el lenguaje; Política; Análisis del discurso; Donald Trump; Sexism; Discourse; Gender-neutral language; Political correctness